The SWELL1-LRRC8 complex regulates endothelial AKT-eNOS signaling and vascular function - Alghanem, Ahmad F; Abello, Javier; Maurer, Joshua M; Kumar, Ashutosh; Ta, Chau My; Gunasekar, Susheel K; Fatima, Urooj; Kang, Chen; Xie, Litao; Adeola, Oluwaseun; Riker, Megan; Elliot-Hudson, Macaulay; et al. (eLife, 2021)
The endothelium responds to numerous chemical and mechanical factors in regulating vascular tone, blood pressure, and blood flow. The endothelial volume-regulated anion channel (VRAC) has been proposed to be mechanosensitive and thereby sense fluid flow and hydrostatic pressure to regulate vascular function. Here, we show that the leucine-rich repeat-containing protein 8a, LRRC8A (SWELL1), is required for VRAC in human umbilical vein endothelial cells (HUVECs). Endothelial LRRC8A regulates AKT-endothelial nitric oxide synthase (eNOS) signaling under basal, stretch, and shear-flow stimulation, forms a GRB2-Cav1-eNOS signaling complex, and is required for endothelial cell alignment to laminar shear flow. Endothelium-restricted Lrrc8a KO mice develop hypertension in response to chronic angiotensin-II infusion and exhibit impaired retinal blood flow with both diffuse and focal blood vessel narrowing in the setting of type 2 diabetes (T2D). These data demonstrate that LRRC8A regulates AKT-eNOS in endothelium and is required for maintaining vascular function, particularly in the setting of T2D.
Keywords: ion channel; mechanobiology; hypertension; diabetes